2022
DOI: 10.3389/fonc.2022.856093
|View full text |Cite
|
Sign up to set email alerts
|

Association of Acupuncture and Auricular Acupressure With the Improvement of Sleep Disturbances in Cancer Survivors: A Systematic Review and Meta-Analysis

Abstract: BackgroundStudies on the efficacy of acupuncture and auricular acupressure on sleep disturbances in cancer patients have been growing, but there is no specific and comprehensive systematic review and meta-analysis. This review aims to evaluate the efficacy and safety of acupuncture and auricular acupressure on sleep disturbances in cancer survivors based on existing randomized clinical trials (RCTs).MethodsFour English-language and four Chinese-language biomedical databases were searched for RCTs published fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 43 publications
(124 reference statements)
0
2
1
Order By: Relevance
“…The effect of auricular acupressure on sleep has been inconsistent. Some researchers have found that auricular acupressure is an effective and safe intervention for improving sleep quality among patients with cancer [14,30], while others found no evidence that auricular acupressure was associated with a reduction in sleep problems [25]. Although we noted a trend for reduction in the total number of parents who reported poorer sleep in AAG, we did not reach statistical signi cance One reason for these negative ndings could be the small sample size in this pilot study.…”
Section: Discussioncontrasting
confidence: 79%
See 1 more Smart Citation
“…The effect of auricular acupressure on sleep has been inconsistent. Some researchers have found that auricular acupressure is an effective and safe intervention for improving sleep quality among patients with cancer [14,30], while others found no evidence that auricular acupressure was associated with a reduction in sleep problems [25]. Although we noted a trend for reduction in the total number of parents who reported poorer sleep in AAG, we did not reach statistical signi cance One reason for these negative ndings could be the small sample size in this pilot study.…”
Section: Discussioncontrasting
confidence: 79%
“…The strength of this pilot study was providing a non-invasive and practical intervention to improve sleep quality, and QOL for those parents in clinical practice. Compared to the tested interventions of exercise [9] and relaxation techniques [20], which are time consuming or need guidance from health care providers during the intervention, auricular acupressure treatment is a safe procedure [25] that is easy for participants to do by themselves at home once the seeded tapes are placed.…”
Section: Discussionmentioning
confidence: 99%
“…Participants were instructed to stimulate each ear point at least 3 times per day. The auriculotherapy protocol used followed the method suggested by TCM, using areas already researched for anxiety and depression: 'Shen Men' 29,33,34 , 'Kidney' [35][36][37] , 'Sympathetic' 34,38,39 , ' Anxiety' 35,39,40 and 'Heart' 35,41,42 . Each week, the ear seeds were removed from the ear in question and placed on the corresponding contralateral ear.…”
Section: Trial Design and Interventionsmentioning
confidence: 99%
“…Recently, several systematic reviews have shown that AA, as an intervention, has beneficial efficacy on maintenance haemodialysis patients (Pei et al., 2021; Yang et al., 2022), leukaemia patients (Jing et al., 2018), cancer survivors (Wan et al., 2022) and adolescents (Gao, Chen, et al., 2020). Meanwhile, AA has been increasingly used in COPD patients, such as deteriorating lung function and sleep quality, but the efficacy has not yet been unified.…”
Section: Introductionmentioning
confidence: 99%